2011
DOI: 10.1155/2011/278963
|View full text |Cite
|
Sign up to set email alerts
|

Osmolarity and Glucose Differentially Regulate Aldose Reductase Activity in Cultured Mouse Podocytes

Abstract: Podocyte injury is associated with progression of many renal diseases, including diabetic nephropathy. In this study we examined whether aldose reductase (AR), the enzyme implicated in diabetic complications in different tissues, is modulated by high glucose and osmolarity in podocyte cells. AR mRNA, protein expression, and activity were measured in mouse podocytes cultured in both normal and high glucose and osmolarity for 6 hours to 5 days. Hyperosmolarity acutely stimulated AR expression and activity, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 78 publications
1
8
0
Order By: Relevance
“…According to the analysis of burst keywords, research hotspots included the physiopathology, genetics, and biomarkers of DN and DR. We speculate that the study of the correlation between the severity of DN and DR will become a new trend. DN and DR have a similar pathogenesis, including oxidative stress ( Jha et al, 2016 ; Kang and Yang, 2020 ), massive accumulation of glycation end products ( Zong et al, 2011 ; Nishad et al, 2021 ), polyol pathway activation ( Lewko et al, 2011 ), protein kinase C ( Kamiya et al, 2003 ), and genetic factors ( Alkayyali and Lyssenko, 2014 ). DN and DR share common clinical risk factors, including age, smoking, hypertension, obesity, and hyperlipidemia ( Wong et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to the analysis of burst keywords, research hotspots included the physiopathology, genetics, and biomarkers of DN and DR. We speculate that the study of the correlation between the severity of DN and DR will become a new trend. DN and DR have a similar pathogenesis, including oxidative stress ( Jha et al, 2016 ; Kang and Yang, 2020 ), massive accumulation of glycation end products ( Zong et al, 2011 ; Nishad et al, 2021 ), polyol pathway activation ( Lewko et al, 2011 ), protein kinase C ( Kamiya et al, 2003 ), and genetic factors ( Alkayyali and Lyssenko, 2014 ). DN and DR share common clinical risk factors, including age, smoking, hypertension, obesity, and hyperlipidemia ( Wong et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Lewko and cols. (34) reported that AKR1B1 gene and protein expressions were elevated in mouse podocytes cultured with high glucose compared to cells cultured under normal glucose concentration. In kidneys from patients with and without DM, AKR1B1 activity was higher in glomeruli and small arteries of those patients with DKD compared to the non-DKD group (35).…”
Section: Discussionmentioning
confidence: 99%
“…For Western blot analysis, 30 μg of total protein was subjected to 8% sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS–PAGE). Proteins were then transferred to polyvinylidene difluoride (PVDF) Immobilion membranes (Millipore, Bedford, MA, USA) by a semidry blotting system (Hoefer Inc, MA, USA) as described previously ( 29 ). Primary antibodies reactive with the insulin receptor β subunit (1:400, rabbit polyclonal, Santa Cruz Biotechnology Inc., CA, USA) and to α-smooth muscle actin (1:2000, mouse monoclonal, Sigma-Aldrich, Poland) were used with secondary antibodies conjugated with alkaline phosphatase (goat anti–rabbit IgG and goat anti-mouse IgG, respectively, Santa Cruz Biotechnology Inc.) The complexes were visualized with 5-bromo-chloro-3-indolyl phosphate (BCIP) and nitro blue tetrazolium (NBT; Sigma-Aldrich, Poland) and photographed with a UVP BioImaging GDS-8000 system (UVP Inc., Upland, CA), using LabWorks 4.0 Image Acquisition and Analysis Software.…”
Section: Methodsmentioning
confidence: 99%